Morphology of the symmetrical morphotypes of Centronella reicheltii Voigt (Fragilariaceae, Bacillariophyceae) from Patagonian environments - Echenique, Ricardo Omar (2004)
The ultrastructure of symmetrical valves of Centronella reicheltii Voigt, resembling the former C. rostafinskii Woloszynska, is studied for the first time, and their morphology is compared with the asymmetrical forms. Valve morphology and morphometry of both morphotypes are similar and only differ in the shape and striation pattern of the valve centre and the arrangement of the arm bases. However, since they occur in environments with different trophic status, the new combination C. reicheltii f. rostafinskii is proposed for the symmetrical valves, because this distinction may provide ecologically useful information.